Stable Redox-Cycling Nitroxide Tempol Has Antifungal and Immune-Modulatory Properties - Hosseinzadeh, Ava; Stylianou, Marios; Lopes, José Pedro; Müller, Daniel C.; Häggman, André; Holmberg, Sandra; Grumaz, Christian; Johansson, Anders; Sohn, Kai; Dieterich, Christoph; Urban, Constantin F. (Frontiers in Microbiology, 2019)
Invasive mycoses remain underdiagnosed and difficult to treat. Hospitalized individuals with compromised immunity increase in number and constitute the main risk group for severe fungal infections. Current antifungal therapy is hampered by slow and insensitive diagnostics and frequent toxic side effects of standard antifungal drugs. Identification of new antifungal compounds with high efficacy and low toxicity is therefore urgently required. We investigated the antifungal activity of tempol, a cell-permeable nitroxide. To narrow down possible mode of action we used RNA-seq technology and metabolomics to probe for pathways specifically disrupted in the human fungal pathogen Candida albicans due to tempol administration. We found genes upregulated which are involved in iron homeostasis, mitochondrial stress, steroid synthesis, and amino acid metabolism. In an ex vivo whole blood infection, tempol treatment reduced C. albicans colony forming units and at the same time increased the release of pro-inflammatory cytokines, such as interleukin 8 (IL-8, monocyte chemoattractant protein-1 (MCP-1) and macrophage migration inhibitory factor (MIF). In a systemic mouse model, tempol was partially protective with a significant reduction of fungal burden in the kidneys of infected animals during infection onset. The results obtained propose tempol as a promising new antifungal compound and open new opportunities for the future development of novel therapies.